Long-term outcomes and prognostic factors of patients with surgically treated pulmonary atypical carcinoid tumors: our institutional experience with 68 patients - Song, Peng; Zang, Ruochuan; Liu, Lei; Dan, Xiayimaier; Gao, Shugeng (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Pulmonary atypical carcinoid (AC) tumors are rare malignant neoplasms and controversy exists regarding management and prognosis. The purpose of this retrospective study was to describe characteristics, and outcomes of patients treated for pulmonary AC tumors. Methods: All patients with a diagnosis of primary pulmonary AC tumor treated from 1999 to 2013 were reviewed. Data collected included demographics, tobacco use, clinical presentation, tumor size and location, pathological stage, immunohistochemical expression, lymph node status, treatment, and survival. Results: There were 55 men and 13 women with a mean age of 55 years. Symptoms were present in 47 patients (69.1%). Twenty-eight patients (41.2%) had a centrally located tumor and 40 patients (58.8%) presented with peripheral tumor localization. Operations included 49 lobectomies, 10 pneumonectomies, 6 bilobectomies, 2 sleeve lobectomies, and 1 wedge resection. There were no peri-operative mortalities. There were 22 patients in stage I, 27 in stage II, 19 in stage III. Twenty-nine (42.6%) patients died and twenty (29.4%) patients relapsed during the follow-up period. The 5- and 10-year survival rates for the 68 cases were 70.6% and 61.8%, respectively. Relapse-free survival was significantly worsened by increasing Ki-67 index (P